The effect of fluorapatite in limestones on the mineral compositions of Portland cement clinkers. (1st March 2021) - Xie, Lilan; Deng, Min; Tang, Jinhui; Liu, Kaiwei
Highlights: Phosphorus-bearing limestone (PL), an industrial raw material from Angola, was used to prepare Portland cement clinker. Influence of fluorapatite on the mineral phase changes and composition of cement clinker has been investigated. Mechanism for the stability of fluorapatite during clinker calcination has been analyzed. Abstract: In this paper, phosphorus-bearing limestone (PL), an industrial raw material from Angola, was used to prepare portland cement clinker. The influence of fluorapatite in PL on the mineral formation and composition of cement clinker was investigated. Raw meals of cements with 0–5.0% P2 O5 were prepared by mixing powdered phosphorus-bearing limestones, normal limestones, clays and iron ore tailings, which all were industrial materials. The mineral composition, morphology and phosphorous distribution in cement clinker have been studied by X-ray diffraction (XRD), laser scanning confocal microscopy (LSCM) and also scanning electron microscopy (SEM). Besides, the burnability of raw materials was also investigated by differential scanning calorimetry (DSC). The results showed that both C3 S and C3 A will gradually decrease with the increase of Ca5 (PO4 )3 F, while C2 S and free CaO will correspondingly increase. During calcination process of cement clinker, natural fluorapatite will decompose accompany with the existence of C2 S at 1100 °C. As a result, fluorine will react with CaO and Al2 O3 to form C11 A7 ·CaF2, preventing the formation of C3 A. And the phosphorous as the C3 P will go into the C2 S and form the stable α'-C2 S-xC3 P, inhibiting the formation of C3 S. Overall, the amount of phosphorus in the clinker presented as follows: C2 S(1.92%)＞C3 S(1.02%)＞Interstitial phase(0.52%).